Immunization against androstenedione to improve the reproductive efficiency in Nilagiri and Sandyno ewes - KUMAR, R ANIL; CHANDRAHASAN, C; SELVARAJU, M (The Indian Journal of Animal Sciences, 2022)
Healthy Nilagiri (90) and Sandyno (90) ewes were selected and allotted to 3 treatment groups of 15 ewes each, viz. AF (Androstenedione immunogen full dose), AH (Androstenedione immunogen half dose) and CC (Control ewes). The experiment was carried out in main and off breeding seasons. The ewes from AF and AH groups were injected with 2 ml (full dose) and 1 ml (half dose) of androstenedione immunogen at 8 and 4 weeks respectively before the start of breeding season. Immunization of ewes against androstenedione had no significant effect on tupping and lambing percentage. The litter size at birth was significantly increased in AF (1.47±0.07) and in AH (1.40±0.07) groups. The litter size was highest in AF Sandyno ewes (1.60±0.09) and in AH Nilagiri ewes (1.43±0.11). The litter size for immunized group ewes was higher during main breeding season (1.40±0.04) than off breeding season (1.23±0.06). Nilagiri (1.31±0.05) and Sandyno (1.33±0.05) ewes had similar litter size at birth. The litter weight at birth and weaning were significantly higher in AF (3.95±0.13 and 13.89±0.61 kg) groups followed by AH (3.80±0.13 and 13.19±0.61 kg) and CC (3.18±0.13 and 10.89±0.66 kg) groups. The weaning percentage/ survivability were similar for all the treatment groups.